Austerity and public sector trade union power: Before and after the crisis. (June 2019) - Schmidt, Werner; Müller, Andrea; Ramos-Vielba, Irene; Thörnquist, Annette; Thörnqvist, Christer
We use a power resources approach to examine the effects of the 2008–2009 financial and economic crisis on public sector trade union power in Germany, Spain, Sweden and the UK, comparing structural, organizational, institutional, societal and political power resources before and after the crisis. Unions' power resources have (at least temporarily) weakened in Spain, with a similar but less pronounced trend in the UK; whereas in Sweden and Germany, one can detect ambiguous but slightly positive signals, which reflect neither the crisis nor opposition to austerity. As well as structural, organizational and institutional power resources, societal and political resources are decisive for public sector trade unions.